2016
DOI: 10.1021/acs.langmuir.6b00039
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effect on Micelle Formation: Molecular Thermodynamic Model Revisited

Abstract: Temperature affects the aggregation of macromolecules such as surfactants, polymers, and proteins in aqueous solutions. The effect on the critical micelle concentration (CMC) is often nonmonotonic. In this work, the effect of temperature on the micellization of ionic and nonionic surfactants in aqueous solutions is studied using a molecular thermodynamic model. Previous studies based on this technique have predicted monotonic behavior for ionic surfactants. Our investigation shows that the choice of tail trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…[18,19] Fort his reason, there have been no reports of templating MOFs using DMF as the solvent. [18,[20][21][22][23][24][25][26][27] Therefore,t ostudy the effects of modulating versus templating during the generation of HP-MOFs,w eh ave developed as ystem that utilizes aliphatic monocarboxylic acids with different lengths that can act as either modulators or templating agents during the generation of HP-MOFs ( Figure 1). By varying the concentrations and the lengths of monocarboxylic acid molecules utilized during the solvothermal synthesis,itisproposed that the mechanism of mesopore formation (modulating or templating) can be effectively tuned, and different variants of hierarchically porous PCN-250 can be obtained due to the different mechanisms.F or the modulation-based mechanism, the monocarboxylic acid molecules act as typical modulators,g enerating mesopores through increased steric effects.I nt he templating-based mechanism, the hydrophobic alkyl chains of the monocarboxylic acid molecules self-assemble into micellular-type structures,w hich act as templates that subsequently generate mesopores within the obtained MOF.…”
mentioning
confidence: 99%
“…[18,19] Fort his reason, there have been no reports of templating MOFs using DMF as the solvent. [18,[20][21][22][23][24][25][26][27] Therefore,t ostudy the effects of modulating versus templating during the generation of HP-MOFs,w eh ave developed as ystem that utilizes aliphatic monocarboxylic acids with different lengths that can act as either modulators or templating agents during the generation of HP-MOFs ( Figure 1). By varying the concentrations and the lengths of monocarboxylic acid molecules utilized during the solvothermal synthesis,itisproposed that the mechanism of mesopore formation (modulating or templating) can be effectively tuned, and different variants of hierarchically porous PCN-250 can be obtained due to the different mechanisms.F or the modulation-based mechanism, the monocarboxylic acid molecules act as typical modulators,g enerating mesopores through increased steric effects.I nt he templating-based mechanism, the hydrophobic alkyl chains of the monocarboxylic acid molecules self-assemble into micellular-type structures,w hich act as templates that subsequently generate mesopores within the obtained MOF.…”
mentioning
confidence: 99%
“…To confirm the tendency of CMC in CHCl 3 toward temperature, we plotted the dependence of CMC on the temperature ( Figure a ). As a result, it was found that the plots are non‐linear, implying a dynamic structural mutation of the micelle in CHCl 3 at around 25 o C. To our best knowledge, there is no report to directly compare our observed non‐linear behavior, although ionic and nonionic surfactants show the similar tendency in aqueous media . Thus, we next measured UV spectra of 0.2 wt% P6 solution in CHCl 3 at various temperatures and plotted the dependencies of transmittance of P6 solution on the temperature for the elucidation of the non‐linear temperature transition of CMC ( Figure b ).…”
Section: Methodsmentioning
confidence: 95%
“…There are several molecular thermodynamic theories to account for ion-specific effects on micellization (Warszyński et al 2002;Moreira and Firoozabadi 2010;Danov et al 2014;Lukanov and Firoozabadi 2014;Zhu and Free 2015;Hao et al 2016;Khoshnood et al 2016;Koroleva et al 2019), but their numerical implementation is complex and computationally prohibitive to atmospheric models. As a way forward, a simple approach to estimate the aggregation number n, thermodynamic potentials and equilibrium constant of the micellization reaction could be based e.g.…”
Section: Extensions Of the Cisa Modelmentioning
confidence: 99%